Political Branding dan Konstruksi Kingship Keluarga Yudhoyono dalam Komunikasi Politik Digital - Ahmad Apriyono; Fachri Muhammad (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2026)
Introduction: In the introduction video of his second son, Agus Harimurti Yudhoyono referred to the newborn, Arjuna Hanyokrokusumo Yudhoyono, as “AHY Junior.” This phenomenon illustrates how a personal event can be strategically constructed into a political message. Objective and scope: This study aims to analyze the meaning of the label “AHY Junior” through the perspectives of Political Branding and Kingship in constructing the narrative of the Yudhoyono family's political dynasty. Method: Employing a constructivist paradigm, this study uses a qualitative descriptive approach with content analysis of the introduction video. Data were collected through media observation and classified into the categories of Political Branding and Kingship. Results: The findings reveal a novel form of political branding in which political identity is constructed from birth through family symbolism. The use of “AHY Junior” reflects the evolution of political dynasties into a modern branding strategy, where the well-established “AHY” identity functions as symbolic capital to strengthen succession narratives and facilitate public acceptance. Conclusion: The “AHY Junior” narrative represents a contemporary political communication strategy that utilizes family symbolism to reinforce legitimacy and sustain political dynasty in the future. ABSTRAKPendahuluan: Dalam video perkenalan putra keduanya, Agus Harimurti Yudhoyono menyebut Arjuna HanyokrokusumoYudhoyono sebagai “AHY junior”. Fenomena ini menunjukkan bagaimana momen personal dikonstruksi menjadi pesan politik yang strategis. Tujuan dan ruang lingkup artikel: Penelitian ini bertujuan menganalisis makna penyebutan “AHY junior” sebagai strategi Political Branding dan Kingship dalam membangun narasi keberlanjutan dinasti politik keluarga Yudhoyono. Metode: Penelitian menggunakan paradigma konstruktivisme dengan metode deskriptif kualitatif melalui analisis isi video perkenalan. Data diperoleh dari observasi terhadap konten media dan diklasifikasikan ke dalam kategori Political Branding dan Kingship. Hasil: Penelitian menemukan bahwa branding politik telah bergeser ke ranah personal melalui identitas keluarga sejak kelahiran. Penyebutan “AHY junior” menunjukkan evolusi dinasti politik ke bentuk yang lebih modern melalui branding sejak dini. Singkatan AHY yang telah melekat sebagai identitas politik menjadi investasi simbolik untuk membangun narasi estafet kepemimpinan dan mempermudah pembentukan simpati publik. Kesimpulan: Narasi “AHY junior” merepresentasikan strategi komunikasi politik yang memanfaatkan simbol keluarga untuk memperkuat legitimasi dan keberlanjutan dinasti politik pada masa depan.